The photographs of Robert Capa and Gerda Taro during the siege of the Alcazar of Toledo (1936). Review of the Magnum Photos and the International Center of Photography catalogue - Vega Hidalgo, Carlos (Revista General de Información y Documentación, 2020)
Robert Capa and Gerda Taro arrived in Spain in August 1936 with their cameras to cover the Civil War. In a few weeks, the couple travelled throughout the loyal territory to take powerful photographs and document republican victories. Their stay in Toledo is one of the least known. In the city, Colonel Moscardó, along with a group of cadets and civil guards who had supported the military uprising, resisted inside the Alcazar from July 22nd. In the archives of the Magnum Agency and the International Center of Photography, several erroneously catalogued photographs taken by Capa and Taro during their stay in Toledo are kept, with incorrect dates and locations. This first stage as reporters in Spain has been much researched due to the famous photograph Death of a Militiaman, but no data has been provided prior to the work done by the reporters during the siege of the Alcazar. It is an objective of study in this investigation to analyse the images have been identified as Toledo, which is possible thanks to certain details that appear in the snapshots and allow us to recognize the urban spaces and approximate dates. Among the images consulted we can make a distinction between the first trip of the reporters at the end of August and the second trip on September 18th, in addition to a differentiation in the formats of the photographic film used by Capa and Taro. Finally, the role of the German reporter is valued, she started as a photojournalist at this stage and has been forgotten after having been the main protagonist in the life and trajectory of the name of Robert Capa. The photographs added in this research show that the reporters shared their cameras and this point allows us to open a new field of investigation to differentiate between Capa and Taro’s work.